Circadian rhythms in innate immunity and stress responses. Issue 4 (3rd January 2020) - Baxter, Matthew; Ray, David W.
Summary: Circadian clocks are a common feature of life on our planet, allowing physiology and behaviour to be adapted to recurrent environmental fluctuation. There is now compelling evidence that disturbance of circadian coherence can severely undermine mental and physical health, as well as exacerbate pre‐existing pathology. Common molecular design principles underpin the generation of cellular circadian rhythms across the kingdoms, and in animals, the genetic components are extremely well conserved. In mammals, the circadian timing mechanism is present in most cell types and establishes local cycles of gene expression and metabolic activity. These distributed tissue clocks are normally synchronized by a central pacemaker, the suprachiasmatic nuclei (SCN), located in the hypothalamus. Nevertheless, most clocks of the body remain responsive to non‐SCN‐derived hormonal and metabolic cues (for example, re‐alignment of liver clocks to altered meal patterning). It has been demonstrated that the clock is an influential regulator of energy metabolism, allowing key pathways to be tuned across the 24‐hr cycle as metabolic requirements fluctuate. Furthermore, clock components, including Cryptochrome and Rev‐Erb proteins, have been identified as essential modulators of the innate immune system and inflammatory responses. Studies have also revealed that these proteins regulate glucocorticoid receptor function, a major drug target and crucial regulator of inflammation and metabolism. Abstract : Circadian clocks play an important role in regulating the immune response. Inflammation in turn regulates the circadian clock.